Biological Characteristics and Thermal Requirements of Telenomus podisi and Trissolcus basalis (Hymenoptera: Scelionidae) in Fresh and Cryopreserved Eggs of Euschistus heros and Nezara viridula (Hemiptera: Pentatomidae) - Oliveira, Regiane Cristina de [UNESP]; Ikuno, Pedro Hiroshi Passos [UNESP]; Pratissoli, Dirceu; Carvalho, José Romário de; Hoback, William Wyatt; Salamina, Bruno Alexis Zachrisson (MDPI, 2024)
Brazil is one of the largest producers of pulses globally, and soybean ranks highly in terms of production. However, pests increase crop production costs and affect oilseed production and quality. Pests are primarily controlled by chemicals, leading to changes in insect pest populations. For example, secondary pests can become primary pests because of the selection of resistant insects and the elimination of natural enemies. Farmers have widely accepted biological control because of its high control efficacy and low environmental contamination risk. Two successful biological control programs in soybean used Telenomus podisi Ashmead (Hymenoptera: Platygastridae) to manage the Neotropical brown stink bug, Euschistus heros (Fabricius) (Hemiptera: Pentatomidae), and Trissolcus basalis (Wollaston, 1858) (Hymenoptera: Scelionidae) to manage the southern green stink bug, Nezara viridula (Linnaeus) (Hemiptera: Pentatomidae), when these pests were the most abundant in soybean-producing regions. To release parasitoids, rearing protocols must be developed in order to optimize production. This study evaluated the effect of temperature on the biological characteristics of T. podisi and T. basalis when fresh or frozen E. heros eggs were provided. Fifty fresh or previously frozen eggs were placed with parasitoids for 24 h in a climate chamber (25 ± 1 °C, 70 ± 10% RH, and 14-h photophase). At the end of this period, the eggs were transferred to other chambers and maintained at different temperatures (19, 22, 25, 28, 31, and 34 ± 1 °C, 70 ± 10% RH, with a 14-h photoperiod). The number of emerging adults from eggs parasitized by T. basalis was lower than that from eggs parasitized by T. podisi. Differences in T. basalis and T. podisi parasitism were observed depending on whether the E. heros eggs were frozen or fresh, but neither development nor emergence were affected. The duration of egg–adult development and the longevity of the two parasitoids were inversely proportional to the temperature increase. The sex ratio of T. basalis and T. podisi progeny was not affected by different temperatures or by the use of frozen or fresh eggs. The estimated number of both parasitoids’ generations corresponded with temperature, reaching 14–15 generations/cycle of soybean for Rio Verde, GO, and 12–14 generations/cycle for Barreiras, BA. Given these characteristics, we conclude that a biological control program using T. podisi can benefit large areas of soybean production by controlling the eggs of phytophagous bugs in soybean crops.
Keywords: biological control; degree day; integrated pest management; parasitism rate; rearing protocol